ChemInform Abstract: Selective C—H Fluorination of Pyridines and Diazines Inspired by a Classic Amination Reaction. Issue 17 (28th April 2014) - Fier, Patrick S.; Hartwig, John F.
Abstract A side selective single‐fluorination of pyridines is presented using commercially available AgF2 as fluorination agent and avoiding tedious multiple step procedures.